Revisions and Dissents : Essays - Gottfried, Paul (Book collections on Project MUSE., 2017)
Paul Gottfried's critical engagement with political correctness is well known. The essays in Revisions and Dissents focus on a range of topics in European intellectual and political history, social theory, and the history of modern political movements. With subjects as varied as Robert Nisbet, Whig history, the European Union election of 2014, and Donald Trump, the essays are tied together by their strenuous confrontation with historians and journalists whose claims about the past no longer receive critical scrutiny. According to Gottfried, successful writers on historical topics take advantage of political orthodoxy and/or widespread ignorance to present questionable platitudes as self-evident historical judgments. New research ceases to be of importance in determining accepted interpretations. What remains decisive, Gottfried maintains, is whether the favored view fits the political and emotional needs of what he calls "verbalizing elites." In this highly politicized age, Gottfried argues, it is necessary to re-examine these prevalent interpretations of the past. He does so in this engaging volume, which will appeal to general readers interested in political and intellectual history.